Advancing trauma care through social media. Issue 1 (21st July 2021) - Luu, Hannah; Keating, Jane; Jacobs, Lenwoth; Gates, Jonathan; Ricaurte, Daniel
Abstract : Social media has become an integral part of everyday life. Because of this, medical representation has become increasingly popular across social media. Medical professionals have begun to recognize the value of social media in areas such as research promotion, mentorship program expansion and collaboration with peers. To date, these online medical communities are being underused in the field of trauma. Trauma centers may benefit by creating a more prominent online presence to allow for the dissemination of critical research, expansion of injury prevention programs and participation in national annual meetings. When used properly, social media can serve as a platform for the advancement of trauma care in a cost-effective manner.